GLB‐13 is associated with oxidative stress resistance in caenorhabditis elegans. Issue 5 (18th March 2013) - Ren, Changhong; Li, Yuan; Han, Rongrong; Gao, Dawen; Li, Weiguang; Shi, Jinping; Hoogewijs, David; Braeckman, Bart P; De Henau, Sasha; Lu, Yiming; Qu, Wubin; Gao, Yan; et al.
Abstract Globins constitute a superfamily of heme‐binding proteins that is widely present in many species. There are 33 putative globins in the genome of Caenorhabditis elegans, where glb‐13 is a homolog of neuroglobin (Ngb) based on sequence analysis and specific expression in neurons. Here we examined whether glb‐13 as well as Ngb is also associated with resistance to reactive oxygen species (ROS) induced by paraquat. Our results showed that the mRNA level of glb‐13 was significantly upregulated after paraquat exposure. Expression of a green fluorescent protein (GFP) reporter gene directed by the glb‐13 promoter was increased by paraquat exposure. The mutant C. elegans strain glb‐13(tm2825) was sensitive to paraquat‐induced oxidative stress. Overexpression of human Ngb (hNgb) in C. elegans neuronal cells can rescue the paraquat sensitive phenotype of the mutant strain. glb‐13 mutation or hNgb overexpression did not affect the expression of antioxidant enzymes such as superoxide dismutase (SOD). To examine the ROS‐scavenging capabilities of hNgb and glb‐13, we further examined the level of ROS in glb‐13 mutant and hNgb transgenic (hNgb‐Tg) worms. There was no statistical difference in ROS levels in the untreated controls; however in paraquat‐treated worms, the ROS level was statistically repressed in the hNgb‐Tg relative to enhanced green fluorescent protein (EGFP)‐Tg worms or wildtype animals. Additionally, the ROS level of glb‐13 mutant was statistically higher than the wildtype animals. Furthermore, hNgb overexpression diminished the ROS level of glb‐13 mutant. In conclusion, hNgb can rescue the ROS sensitive phenotype of the glb‐13 mutant strain. The protein GLB‐13 seems to have an hNgb‐like function, suggesting the importance of the globin protein family in maintaining the homeostasis of ROS signals. Our data provided evidence for the first time that glb‐13 is associated with the resistance against oxidative stress‐induced toxicity. © 2013 IUBMB Life, 65(5)423–434, 2013.